1978
DOI: 10.1002/aic.690240519
|View full text |Cite
|
Sign up to set email alerts
|

A method for the study of performance of a single spherical particle with nonuniform catalytic activity

Abstract: In recent years, there has been increasing interest in porous catalysts which contain nonuniform activity. For example, Kasaoka and Sakata ( 1968), Villadsen ( 1976), Corbett and Luss (1974), Shadman-Yazdi and Petersen (1972), and Becker and Wei (1977u, b) have recently developed theoretical models to describe the performance of catalysts with nonuniform activity. Some catalysts contain nonuniform activity as a result of preparation methods employed, while others develop this feature because of poisoning. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1982
1982
1986
1986

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Indeed, this has been demonstrated to be the case by Shadman-Yazdi and Petersen (1972) and by Corbett and Luss (1974) who modeled the performance of spherical catalyst particles under isothermal conditions for the series reactions: A + B + C. They showed that selectivity is a strong function of the distribution of activity within the catalyst particle. Similar conclusions were reached by Ernst and Dougherty (1978) who modeled the reaction of deuterium exchange with neopentane over nonuniformly activated catalyst pellets.…”
Section: Introductionsupporting
confidence: 77%
“…Indeed, this has been demonstrated to be the case by Shadman-Yazdi and Petersen (1972) and by Corbett and Luss (1974) who modeled the performance of spherical catalyst particles under isothermal conditions for the series reactions: A + B + C. They showed that selectivity is a strong function of the distribution of activity within the catalyst particle. Similar conclusions were reached by Ernst and Dougherty (1978) who modeled the reaction of deuterium exchange with neopentane over nonuniformly activated catalyst pellets.…”
Section: Introductionsupporting
confidence: 77%
“…This recognition has been both theoretical (cf. Kasaoka and Sakata, 1968; Minhas and Carberry, 1969; Shadman-Yazdi and Petersen, 1972;Corbett and Luss, 1974; Smith and Carberry, 1975;Smith, 1976;Villadsen, 1976;Becker and Wei, 1977;Nystrom, 1978;Ernst and Daugherty, 1978) and experimental (cf. Michalko, 1966;Summers and Hegedus, 1978;Hegedus et al, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…The deuterium-neopentane exchange (DNE) reaction was employed in the study (Dwyer et al, 1968;Ernst and Daugherty, 1978;Ernst and Wei, 1975). The theory is based upon the work of Wei and Prater (1962) and Wei (1 962a, b).…”
mentioning
confidence: 99%
“…The theory is based upon the work of Wei and Prater (1962) and Wei (1 962a, b). Ernst and Daugherty (1978) showed that the highly coupled system of rate equations which describe the behavior of Dexchanged hydride species such as neopentane can be uncoupled if the following transformation is made. Wang and Varma (1980) solved the intraparticle diffusionreaction problem for a catalyst pellet that has an activity profile described by the equation k ( x ) = m z ( 1 -x )~.…”
mentioning
confidence: 99%